2023
DOI: 10.3390/coatings13081410
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cu Substitution on the Properties of Hydroxyapatite Targets and Deposited Coatings

Abstract: In addressing the issue of optimizing the mechanical and electrochemical properties of hydroxyapatite (CaP) materials for biomedical applications, this research explored the incorporation of copper (Cu) into the material and scrutinized its impact through various processing stages, from powders to ceramics and finally to coatings. Our investigation indicated that the integration of CuO into CaP significantly changed the lattice parameters of hydroxyapatite from manufactured powders to sintered targets, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Their action contributes not only to osteogenesis but also to a decrease in bacterial growth. Strong antibacterial properties of copper ions could prevent peri-implantitis-inflammation around a newly installed implant [11]. Previous studies have demonstrated a clear antibacterial effect, with a death rate of about 22% at a concentration of Cu 2+ ions at approximately 12 mol.% in the β-TCP structure, and acceptable cytocompatibility [12].…”
Section: Introductionmentioning
confidence: 99%
“…Their action contributes not only to osteogenesis but also to a decrease in bacterial growth. Strong antibacterial properties of copper ions could prevent peri-implantitis-inflammation around a newly installed implant [11]. Previous studies have demonstrated a clear antibacterial effect, with a death rate of about 22% at a concentration of Cu 2+ ions at approximately 12 mol.% in the β-TCP structure, and acceptable cytocompatibility [12].…”
Section: Introductionmentioning
confidence: 99%